2017
DOI: 10.4314/ahs.v17i1.16
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial to assess the effect of a ketamine infusion on tourniquet hypertension during general anaesthesia in patients undergoing upper and lower limb surgery

Abstract: Background: Tourniquet hypertension arising from tourniquet inflation remains a primary concern to the anaesthetist. One drug commonly used to manage tourniquet hypertension is ketamine. No studies have examined the effect of ketamine on tourniquet hypertension for a period of more than one hour or an infusion of the same. Objective: To compare the effect of an intravenous infusion of ketamine versus placebo on tourniquet induced hypertension in patients undergoing upper and lower limb surgery under general an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…In cases of extensive lower limb injuries, tourniquets may be applied in the emergency department to reduce bleeding. However, prolonged tourniquet use can cause pain and restlessness in patients, as well as significant hemodynamic fluctuations [60]. Studies have shown that ultrasoundguided iliac fascia plane block or femoral nerve block can effectively alleviate tourniquet-related discomfort [61,62].…”
Section: Lower Limb Injuriesmentioning
confidence: 99%
“…In cases of extensive lower limb injuries, tourniquets may be applied in the emergency department to reduce bleeding. However, prolonged tourniquet use can cause pain and restlessness in patients, as well as significant hemodynamic fluctuations [60]. Studies have shown that ultrasoundguided iliac fascia plane block or femoral nerve block can effectively alleviate tourniquet-related discomfort [61,62].…”
Section: Lower Limb Injuriesmentioning
confidence: 99%
“…They reported reduced frequency of hypertension in ketamine group (4.6%) versus the saline group (26%); p-value <0.05. 7 According to literature review, no single technique/medication has been shown to completely prevent tourniquet induced hypertension. Rationale of this study was that currently, at our local institutes, no drug is used for prevention of tourniquet induced hypertension, however, tourniquet induced hypertension is treated with injection Glyceryl trinitrate, increasing the depth of anaesthesia and analgesia.…”
Section: Introductionmentioning
confidence: 99%
“…Continuing with the theme of surgery in Africa, researchers from Kenya report on the effect of a ketamine infusion on tourniquet hypertension during general anaesthesia in patients undergoing limb surgery 16 ; while Alghadir and others report on the effect of posture on swallowing 17 , with Kamau reporting on the effect of a preanaesthesia clinic consultation on adult patient anxiety at a tertiary hospital in Kenya 18 . Now to pharmacology.…”
Section: 11mentioning
confidence: 99%